Some observations on tiaprost mediated induced spawning of goldfish Carassius auratus (Linnaeus) - Jadtap, H S; Ghumare, S S; Borate, H B; Wakcharkar, R D; Ravindranathan, T (Indian Journal of Fisheries, 2011)
Selected brood of goldfish, Carassius auratus were subjected to induced spawningby tiaprost, a prostaglandin analogue and were compared with control. Spawningacts of female and chasing sex play of male in experimental groups were observedby 1 h of tiaprost administration and continued upto 6 h, followed by spawningat 72 h. The spawning efficacy of the above groups after 72 h were recorded indifferent instances as: spawning response 50-55%, fecundity 2,000-3,000 eggs/female (30 g aprox.) and fertilization range 80-85% over non-spawn response ofcontrol groups within those hours. The non-induced males of experimental groupsproduced 45.6 Â± 9.41 pi milt over 10.2 Â± 2.46 pi of the control group at 12 h, whichis highly significant